Hungarian Monitoring, 20 June 1990 . [Magyar rádiófigyelő], 1990. június 20 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Corrupt one-party systems in Africa undermined - Split possible within the Communist Party of the Soviet Union - Walesa's presidential plans - Honecker on the pro-terrorist accusations - Speculations from Prague on the formation of a government Domestic Affairs: - József Antall in talks in the FRG - Árpád Göncz recommends candidates for the posts of Supreme Court chairman and Chief Prosecutor - Lajos Für on Hungary's exit from the Warsaw Pact Economy: - Hungarian government launches program to boost enterprise - Financial background of agriculture - Budapest Stock Exchange reforms - Deterioration in willingness to pay taxes in Hungary Külpolitika: - megrendülő korrupt egypártrendszerek Afrikában - szakadás lehet a szovjet kommunista pártban - Walesa elnöki terveiről - Honecker a terrorpártolás vádjáról - kormányalakítási spekulációk Prágából Belpolitika: - Antall József az NSZK-ban tárgyal - Göncz Árpád javaslatot tesz a Legfelsőbb Bíróság elnökének és a Legfőbb Ügyész személyére - Für Lajos a Varsói Szerződésből való kilépésről Gazdaság: - a magyar kormány vállalkozásélénkítő programot indít - a mezőgazdaság anyagi háttere - újjáalakult a Budapesti Értéktőzsde - romló adómorál Magyarországon